2020
DOI: 10.1002/asl.948
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the 2018 UK summer heatwave to local sea temperatures and soil moisture

Abstract: The impact of local climate conditions on air temperatures during a hot summer period over the United Kingdom in 2018 is studied using simple sensitivity experiments with a state‐of‐the‐art regional numerical weather prediction system. The experiments are designed to investigate the influence of sea surface temperature (SST) and soil moisture on the air temperatures over land. They involved applying changes to the analysed SST and soil moisture patterns with magnitudes consistent with the differences between f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Southern England recorded only 7.1mm of rain through June, its second driest June in a series from 1862, behind only 1925. This established dry soils which increased the high maximum temperatures experienced in southeast England during late July (Petch et al ., ).…”
Section: Summer 2018 and Its Historical Contextmentioning
confidence: 97%
See 1 more Smart Citation
“…Southern England recorded only 7.1mm of rain through June, its second driest June in a series from 1862, behind only 1925. This established dry soils which increased the high maximum temperatures experienced in southeast England during late July (Petch et al ., ).…”
Section: Summer 2018 and Its Historical Contextmentioning
confidence: 97%
“…Using the Met Office Unified Model in regional configuration, Petch et al . () have undertaken sensitivity experiments to quantify this impact. Experiments were conducted in which the SSTs within the model domain were reduced by 1.5 or 3.0 degC across the whole domain, running 5‐day forecasts over an 11‐day period in late July 2018.…”
Section: Regional Sstmentioning
confidence: 99%
“…SST uncertainty and ice concentration (IC) fields are also produced. Although designed for use in NWP, OSTIA data have found a variety of applications including ocean (e.g., [2]) and atmospheric (e.g., [3]) reanalyses and have been used in numerous scientific studies (e.g., recently [4,5]). Since the OSTIA system was originally set up and documented in [1], a variety of changes have been made.…”
mentioning
confidence: 99%
“…While anthropogenic climate change could be responsible for certain proportion of these record-breaking warmth and precipitation deficits, natural variability was also indispensable factor 4 6 . Previous studies have suggested several drivers for these 2018 summertime European heatwave and drought events, including persistent blocking 2 , 6 , subtropical ridge or tropical continental air flow 5 , 7 , an exceptionally strong stationary Rossby Wave-7 pattern 8 , 9 , prevalence of the positive phase of the summer North Atlantic Oscillation (NAO) 5 , 9 , the Atlantic sea-surface temperature (SST) tripole pattern 5 , 10 , local SST and soil moisture content 5 , 11 . Moreover, improved seasonal 10 and short-term 11 predictions have been made using reasonable representations of the SST tripole pattern and local SST/soil moisture content, respectively, for the 2018 summer dry and hot conditions.…”
Section: Introductionmentioning
confidence: 99%
“…S1). Among the previous studies for the European extreme weathers in the summer of 2018, none of them focused on the dynamic drivers for the heatwave event in the second half of July [1][2][3][4][5][6][7][8][9][10][11] . In this study, we investigated the dynamic drivers of the heatwaves over northwestern Europe that occurred from mid-July to early August 2018, with an emphasis on the regional heatwave events in Scandinavia (SC) and Western Europe (WE).…”
mentioning
confidence: 99%